Gilcrest: A house for the president of a record company, Hollywood California - Robert Mangurian (Oz, 1987)
Gil: I enjoyed dinner last week and look forward to our next meeting. Enclosed are two copies of the agreement. Some notes follow that should make clearer certain points of the Standard Agreement. Also, I thought I would elaborate some on our discussion concerning the present design.